In vivo nonlinear optical imaging to monitor early microscopic changes in a murine cutaneous squamous cell carcinoma model. Issue 8 (15th October 2014) - Thomas, Giju; van Voskuilen, Johan; Truong, Hoa; Gerritsen, Hans C.; Sterenborg, H.J.C.M.
Abstract : Early detection of cutaneous squamous cell carcinoma (cSCC) can enable timely therapeutic and preventive interventions for patients. In this study, in vivo nonlinear optical imaging (NLOI) based on two‐photon excitation fluorescence (TPEF) and second harmonic generation (SHG), was used to non‐invasively detect microscopic changes occurring in murine skin treated topically with 7, 12‐dimethylbenz(a)anthracene (DMBA). The optical microscopic findings and the measured TPEF‐SHG index show that NLOI was able to clearly detect early cytostructural changes in DMBA treated skin that appeared clinically normal. This suggests that in vivo NLOI could be a non‐invasive tool to monitor early signs of cSCC.In vivo axial NLOI scans of normal murine skin (upper left), murine skin with preclinical hyperplasia (upper right), early clinical murine skin lesion (lower left) and late or advanced murine skin lesion (lower right). Abstract : In vivo nonlinear optical imaging (NLOI) based on two‐photon excitation fluorescence (TPEF) and second harmonic generation (SHG) was used to non‐invasively detect microscopic changes in murine skin treated topically with 7, 12‐dimethylbenz(a)anthracene (DMBA). NLOI was able to clearly detect early cytostructural changes in DMBA treated skin that appeared clinically normal. The method has great potential as a diagnostic non‐invasive tool to monitor early cancerous changes in skin..